Studi Stabilitas Baku Pembanding Glukosamin Hidroklorida: Penerapan ISO 17034:2016 dalam Memastikan Kualitas dan Validitas Pengujian Farmasi - Isnaeni, Neni (Eruditio : Indonesia Journal of Food and Drug Safety, 2025)
Reference standards are essential in drug and food control to ensure the quality and validity of test results. According to ISO 17034:2016, the Center for National Quality Control Laboratory of Drugs and Food (PPPOMN), as a producer of reference materials, must evaluate and monitor the stability of the standards it produces. Stability testing is critical to maintain product quality during storage and use. However, PPPOMN-developed reference standards had not undergone stability testing to determine shelf life. This study therefore conducted a stability assessment of the Glucosamine hydrochloride reference standard to ensure stability during transportation, distribution, and storage. Long-term stability tests were conducted at 4–8°C at 0 months (control), 72 months, and 144 months. Short-term stability tests were performed at 25°C and 60°C for 72, 120, 168, and 240 hours, with 0 hours as the control. Stability analysis was performed using validated High-Performance Liquid Chromatography (HPLC), and analyte stability was assessed using a t-test. Results indicated that the Glucosamine hydrochloride secondary reference standard remained stable under recommended storage conditions for 144 months and at distribution temperatures up to 60°C for 240 hours (t-count = 0.976). These findings demonstrate that the reference standard maintains its quality under specified conditions, ensuring the reliability and validity of pharmaceutical testing. The study concludes that the glucosamine hydrochloride reference standard has guaranteed quality and can be used as long as it is stored under the recommended conditions and shelf life. Information regarding storage conditions and shelf life can be included on the reference standard label.